PENGARUH JUMLAH SUDU TERHADAP KINERJA TURBIN ANGIN SUMBU VERTIKAL TIPE DARRIEUS-H NACA 3412 DENGAN SUDUT PITCH 00 - Arif Rochman Fachrudin (Universitas Lambung Mangkurat, 2018)
Potential and utilization of renewable energy in Indonesia is still very small. Oneof the renewable energy sources is wind energy. The use of wind turbines, windenergy is converted into mechanical energy and can then generate electricitythrough a generator. Wind turbines are environmentally friendly, inexpensive,easy to operate and easy to maintain. The purpose of this study was to determinethe effect on the performance of the number of blades and wind speed for thevertical axis wind turbine type darrieus H with the NACA profile 3412 with apitch 0o angle. This study uses an experimental method, with a number of bladesand varying wind speeds. The number of blades given is 2 units, 3 units and 4units. The speed of the given wind is 3.3 m / s, 3.5 m / s, 3.7 m / s, and 3.9 m / s.Performance is obtained from the electrical power produced by a generatormounted on the turbine axis. The results showed that the turbine performance wasinfluenced by the number of blades. The highest power in the number of bladeswas 4 units at a wind speed of 3.3 m / s which resulted in electric power of 5.166Watt. The lowest electric power is produced on turbines with a number of units of2 units at a wind speed of 3.3 m / s, which is 3.0173 Watts. The blade is 2 unitsand 3 units, at a wind speed of 3.3 m / s; 3.5 m / s; 3.7 m / s and 3.9 m / s, theelectrical power produced is relatively the same, while in blades 4 units, thedifference in wind speed (3.3 m / s; 3.5 m / s; 3.7 m / s and 3.9 m / s) produce adifference in the electrical power produced